SLEEP DISTURBANCES AND OPTIMIZATION IN NIGHT-SHIFT WORKERS - A LITERATURE REVIEW - Jakub Roszak; Oliwia Sójkowska-Sławińska; Anna Leśniewska; Patryk Macuk; Michał Gniedziejko; Paulina Bernecka; Bartosz Michał Skorupski; Natalia Strumnik (International Journal of Innovative Technologies in Social Science, 2026)
Sleep is a fundamental biological process essential for physical recovery, cognitive performance, metabolic regulation, hormonal balance, and mental health. Night and rotating shift workers constitute a high-risk population for sleep disturbances due to chronic circadian misalignment, irregular sleep-wake schedules, and elevated occupational stress. This narrative review synthesizes current evidence on sleep physiology, specific sleep disorders, and the acute and chronic health consequences of shift work, integrating insights from occupational health and sports recovery research. Shift work is consistently associated with altered sleep architecture, reduced slow-wave and REM sleep, and conditions such as Shift Work Sleep Disorder and social jet lag, leading to impaired vigilance, increased error risk, and mood dysregulation. Long-term exposure to night work is linked to adverse cardiometabolic outcomes, including hypertension, obesity, metabolic syndrome, type 2 diabetes, and cardiovascular disease, as well as disrupted eating behaviors and unfavorable meal timing. Emerging evidence also indicates neurological consequences such as accelerated brain aging, cognitive decline, and increased vulnerability to neurodegenerative and seizure disorders. Additionally, hormonal dysregulation involving melatonin, cortisol, sex hormones, and circadian clock gene expression may contribute to reproductive disturbances, immune dysfunction, and increased cancer risk. The review further discusses organizational- and individual-level interventions, including optimized shift scheduling, strategic light exposure, napping, sleep hygiene, meal timing, physical activity, and cognitive-behavioral strategies, highlighting practical approaches to mitigate sleep disturbances and improve health and performance among night-shift workers.